Riboflavin Biosynthesis and Overproduction by a Derivative of the Human Gut Commensal Bifidobacterium longum subsp. infantis ATCC 15697 - Solopova, Ana; Bottacini, Francesca; Venturi degli Esposti, Elena; Amaretti, Alberto; Raimondi, Stefano; Rossi, Maddalena; van Sinderen, Douwe (Frontiers in Microbiology, 2020)
Riboflavin or vitamin B2 is the precursor of the essential coenzymes flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD). Despite increased interest in microbial synthesis of this water-soluble vitamin, the metabolic pathway for riboflavin biosynthesis has been characterized in just a handful of bacteria. Here, comparative genome analysis identified the genes involved in the de novo biosynthetic pathway of riboflavin in certain bifidobacterial species, including the human gut commensal Bifidobacterium longum subsp. infantis (B. infantis) ATCC 15697. Using comparative genomics and phylogenomic analysis, we investigated the evolutionary acquisition route of the riboflavin biosynthesis or rib gene cluster in Bifidobacterium and the distribution of riboflavin biosynthesis-associated genes across the genus. Using B. infantis ATCC 15697 as model organism for this pathway, we isolated spontaneous riboflavin overproducers, which had lost transcriptional regulation of the genes required for riboflavin biosynthesis. Among them, one mutant was shown to allow riboflavin release into the medium to a concentration of 60.8 ng ml-1. This mutant increased vitamin B2 concentration in a fecal fermentation system, thus providing promising data for application of this isolate as a functional food ingredient.